1993
DOI: 10.1038/bjc.1993.47
|View full text |Cite
|
Sign up to set email alerts
|

Infrequent chromosome allele loss in fibrolamellar carcinoma

Abstract: Summary As yet, there is no reported study of chromosome allele loss in fibrolamellar carcinoma (FLC), a distinct, rare variant of hepatocellular carcinoma (HCC). We searched for evidence of allele loss in FLC using 18 DNA probes for 10 chromosomes and compared the pattern of loss with our series of HCC. Two of the probes, AMS32 (lq42-43) and cMS621 (5p) showed allele losses in one tumour, while other probes showed no loss. The frequency of allele loss in FLC was much lower than in HCC, which may be associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 15 publications
0
6
1
Order By: Relevance
“…Ding et al examined five cases of fibrolamellar carcinoma for loss of heterozygosity at 18 sites and found only two allele losses in 55 informative loci, both occurring in the same patient. 45 This allele loss rate of 3.6% was significantly lower than the rate of 16.1% that they previously described in 16 cases of classic hepatocellular carcinoma using the same methods. 46 Orsatti et al examined the ploidy of 12 cases of fibrolamellar carcinoma and 10 cases of hepatocellular carcinoma.…”
Section: Genetics and Epigeneticscontrasting
confidence: 51%
“…Ding et al examined five cases of fibrolamellar carcinoma for loss of heterozygosity at 18 sites and found only two allele losses in 55 informative loci, both occurring in the same patient. 45 This allele loss rate of 3.6% was significantly lower than the rate of 16.1% that they previously described in 16 cases of classic hepatocellular carcinoma using the same methods. 46 Orsatti et al examined the ploidy of 12 cases of fibrolamellar carcinoma and 10 cases of hepatocellular carcinoma.…”
Section: Genetics and Epigeneticscontrasting
confidence: 51%
“…Cytogenetic studies and other methodologies for examining large cytogenetic abnormalities have shown relative chromosomal stability in FLC, compared with typical HCC [2,4,13], and have identified a limited number of areas of interest, principally gains on chromosome 1q [2,4]. Positional mapping of typical HCC has further narrowed the regions of interest for the 1q oncogene:1q21-q22 [14], 1q23.1-q24.2 [5], 1q32.1 [5], and 1q43-q44 [5].…”
Section: Discussionmentioning
confidence: 97%
“…The frequency of allelic loss evaluated by polymerase chain reaction has been shown to be lower in fibrolamellar carcinoma compared with conventional hepatocellular carcinoma. 41 These tumors have also been shown to lack intratumor heterogeneity as detected by DNA fingerprinting Figure 3 Kaplan-Meier curve demonstrating 5-year survival in fibrolamellar carcinomas with cytogenetic abnormalities versus those without cytogenetic abnormalities (33% vs 80%, P ¼ 0.1).…”
Section: Discussionmentioning
confidence: 99%